Effect of Porphyromonas gingivalis infection on leukocyte count in rat model of diabetes mellitus - Safira Niza Ulfita; Agustin Wulan Suci Dharmayanti; Budi Yuwono (Majalah Kedokteran Gigi Indonesia, 2018)
Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia and become the third cause of death in Indonesia. The most common oral complications occured in DM is periodontitis. Porphyromonas gingivalis (Pg) is the main etiology of periodontitis, one of periodonthopathogen relate to systemic disease. However this theory still controversial, DM and periodontitis have the same pathogenesis, thus are cellular changes. Pg is predicted affect the total leukocytes count in DM. The aim of this study was to determine the effect of Pg infection to total leukocytes count in DM rat model. The rat model of DM was obtained by injection of streptozotocin with different dosage for 5 days sequentially then injected by Pg on distobuccal and distopalatal sulcus of the maxillary first molars for 19 days with interval 3 days. The total leukocytes were calculated manually by Neubauer improved cell counting chamber. The results demonstrated that rat model of DM which injected by Pg has the lowest total leukocytes count. Therefore, Pg infection decreased the total leukocytesin DM rat model.